Consistency in fruit preferences across the geographical range of the frugivorous bats Artibeus , Carollia and Sturnira (Chiroptera) - Parolin,Lays C. (2016)
Abstract The frugivorous phyllostomid bat genera Artibeus , Carollia and Sturnira are important seed dispersers in the Neotropics, and exhibit supposed preferences for fruits of the genus Ficus , Piper and Solanum , respectively. We performed a quantified literature review to test the hypothesis that interactions with plants are consistent throughout the bats´ geographic ranges. Through an extensive literature review we obtained a total of 4,448 records of fruit consumption from 180 publications. To test which fruits were most frequently consumed across the Neotropical region and in each of its component countries these data were organized by bat species and country. In general, considering the 176 botanical genera eaten by these bats, the results showed a high consumption frequency of Ficus (24.0%) by Artibeus , Piper (38.7%) by Carollia and Solanum (31.0%) by Sturnira . Additionally, our findings support the hypothesis of diet consistency throughout the geographic range of these genera. We suggest that this consistency is related to the wide distribution of the study groups (both bats and plants), the phenology of the zoochoric species consumed, the spatial fidelity of bats and the foraging patterns of the different bat species.